Trust as mediating effect on the factors of technology adoption in hotels / Zubi Abdelati Ibrahim and Faiz Izwan Anuar - Ibrahim, Zubi Abdelati; Anuar, Faiz Izwan (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2024)
The purpose of this study is to explore the effect of perceived usefulness, perceived ease of use, and perceived credibility as independent variables, on the mobile application adoption in the Malaysian hotels as dependent variable. To further explore the relationships in this study, the research introduced Trust as mediating variable in the middle between perceived usefulness, perceived ease of use, and perceived credibility on the mobile application adoption. In addition, the researcher reviewed the recent published literature alongside five underpinning theories about technology adoption and behavioral studies, and that was in order to define the research gap that this studying is intending to fill. Moreover, the researcher has followed the quantitative research methodology, by selecting 196 hotels as research sample out of 388 hotels in Selangor and Kuala Lumpur. The researcher adopted a semi structured questionnaire from the published literature. In this study, the researcher has used IBM SPSS as mean of data analysis, in addition to IBM AMOS for testing the goodness of the model fit. The research has found strong and significant relationship between perceived usefulness, perceived credibility and Trust with mobile application adoption, while the findings revealed that perceived ease of use observed to be insignificant with mobile application adoption. Furthermore, the researcher found that Trust played a significant mediating role between perceived usefulness, perceived ease of use, and perceived credibility on the mobile application adoption. Finally, the researcher discussed the findings of this study in light with the published literature and presented the implications of this study practically and theoretically, alongside the future research recommendation.